TEAD-targeting small molecules induce a cofactor switch to regulate the Hippo pathway - Alissa D. Guarnaccia; Thijs J. Hagenbeek; Wendy Lee; Noelyn Kljavin; Meena Choi; Benjamin Tombling; Carsten Peukert; Gözde Ulas; Vasumathi Kameswaran; Daniel Le; Sayantanee Paul; Samir Vaidya; et al. (Proceedings of the National Academy of Sciences, 2025)
TEAD proteins are the main transcriptional effectors of the Hippo signaling pathway and a clinical-stage pharmacological target in oncology. Most TEAD-targeting small molecules are designed to disrupt interaction between TEAD and the oncogenic transcriptional activators YAP and TAZ. Here, we uncover an alternative mechanism for a subset of TEAD lipid pocket-binding molecules. We report that select sulfonamide-containing TEAD-targeting compounds enhance the interaction between TEAD and the transcriptional repressor VGLL4. Chemically induced VGLL4–TEAD complexes confer an antiproliferative effect by outcompeting YAP–TEAD complexes at chromatin. This cofactor switch from YAP to VGLL4 impacts transcriptional networks, including influencing the expression of genes involved in cellular proliferation and mechanosignaling. We demonstrate that VGLL4 is required for an antiproliferative response to these sulfonamide-containing compounds by counteracting YAP. We show that VGLL4 overexpression can confer sensitivity to these compounds in Hippo-driven cell lines, and we further show that genetic deletion of VGLL4 oblates cellular responsiveness to these molecules in cells and in vivo. Our data reveal a category of TEAD inhibitors that act as “molecular glues” toward the repressive VGLL4–TEAD interaction. These findings open up understandings for curbing the oncogenic activity of Hippo pathway deregulation in cancer, and identify glue-like molecules that promote transcriptional repression.